Muslim Bengal writes back: a study of Rokeya’s encounter with and representation of Europe - Hasan, Md. Mahmudul (Routledge, 2016)
Despite its exploitative nature, colonialism facilitated continuous cultural exchanges between Muslim Bengal, home of the writer Rokeya Sakhawat Hossain, and the European metropolis. Although Rokeya never visited Europe, she was exposed to European literature, overcame sociocultural constraints, and thus became engaged in a complex critique and assessment of European culture in relation to her own environment. This article explores the ways in which, as a writer, educationalist, activist and wife of a civil servant, Rokeya had opportunities to interact directly with European women and indirectly with European men. Importantly, she made available to her readers an interpretative summary of Marie Corelli’s novel The Murder of Delicia (1896), informed them about the Victorian “woman question” and identified comparable gender norms in Europe and India. This article discusses how Rokeya broke through the iron gate of purdah practices prevalent at the time, availed herself of opportunities to explore European culture, and commented on the condition of women.